Race and justice in an Australian court: Prosecuting homicide in Western Australia, 1830-1954 - Finnane, Mark (Australian historical studies, 2016)
Contemporary rates of incarceration of Indigenous peoples in Australia are generally seen as quite recent in origin, an unwanted outcome of the emergence of Indigenous people into full citizenship from the 1960s. Yet for only relatively short periods were Indigenous people in Australia excluded from the full implications of the rule of law in its mode of criminal jurisdiction; for the most part, they were considered British subjects. Having been brought into criminal jurisdiction how did they fare? While much can be learned from archival research at the case level, we propose here that qualitative studies are best examined in quantitative context. In this article, the first ever quantitative study of Australian homicide over long periods of time, we consider how criminal justice worked for Indigenous and non-Indigenous defendants, identifying how many defendants in each group were prosecuted, and their varying treatment at trial process, outcome and sentence.